An efficient time-domain simulation method for multirate RF nonlinear circuits - Oliveira, Jorge dos Santos Freitas de (2009)
This paper describes a new computer-aided design tool especially conceived for the efficient time-domain simulation of highly heterogeneous nonlinear wireless communication circuits, i.e., combining RF and baseband analog circuitry and digital components. Using multirate Runge–Kutta algorithms within a multitime framework, to benefit from the different rates of variation of slowly varying (latent) and fast-varying (active) currents and voltages (state variables), we managed to solve the envelope transient regime of circuits excited by AM and PM RF carriers, in a highly efficient way. Indeed, with the adoption of convenient sampling rates for the multiple time representations of the slowly varying and fast-varying state variables, gains of more than one order of magnitude in simulation time are reported, even for an illustrative circuit example of very small size.